Development of ICT Based PBL Platform - Pandit, C. M.; Panpat, B. R. (Journal of Engineering Education Transformations, 2019)
Since Vishwaniketan's Institute of Management Entrepreneurship and Engineering Technology (ViMEET) is affiliated to Mumbai University, it has to follow the traditional teaching learning methodology. Daily routine of typical classroom teaching and feeling of unworthiness for few courses makes learning process boring and irritating for students. But following PBL practices along with traditional teaching learning methodology can add spice to the professional life of teachers and students. Though, PBL is innovative tool for teaching and learning process, but following the practices of traditional teaching learning methodology along with PBL approach increases workload on teachers and students. Maintaining the details of all PBL activities manually can be a cumbersome process for teachers. In such case integration of ICT to PBL can be a great help. So far participation of ICT in PBL is in online learning, online feedback, for assignment submission etc. This paper proposes the architecture of web based tool which automates PBL activities and makes it paperless. This tool is first of its kind in the institution and in whole Mumbai University.